Calibration and validation of a dynamic model of the UC San Diego NHERI 6-DOF Large High‐Performance Outdoor Shake Table - Lai, C.-T.; Conte, J.P. (Engineering structures, 2025)
This paper presents a systematic, step-by-step methodology for calibrating the parameters of the multi-physics model of the six-degree-of-freedom (6-DOF) NEHRI-UCSD Large High-Performance Outdoor Shake Table (LHPOST6) under bare table condition, using an extensive set of experimental characterization test data. The linear least squares method, applied in both the time and frequency domains, is used to identify: (1) the polytropic indices of the nitrogen gas within the pneumatic cylinders (hold-down struts), (2) the effective inertial properties of the rigid platen and moving parts of the components attached to it, (3) the characteristics of the energy dissipation mechanisms between the platen and interacting components (e.g., friction and viscous damping forces), (4) the fourth-stage servovalve spool dynamics in the frequency domain for both the horizontal and vertical actuators, and (5) the effective bulk modulus and nonlinear flow curve parameters characterizing the pressurized hydraulic fluid and its flow through the actuator chambers. Additionally, the model calibration methodology includes an effective procedure for extracting the inertial and dissipative forces acting on the shake table platen by analyzing the hysteresis loops generated by the LHPOST6 during periodic (triangular and sinusoidal) wave tests. The mechanics-based model of the LHPOST6 and its calibrated parameters are validated through a tri-axial earthquake ground motion test, following a three-phase strategy: Phase 1 at the subsystem level, Phase 2 at the open-loop system level, and Phase 3 at the closed-loop system level. Comparisons between numerically simulated and experimental results show that the calibrated model accurately captures the dynamic response behavior of the LHPOST6. This validated model of the LHPOST6 will be used in future studies to: (i) enhance shake table performance by improving the tuning procedure of the controller and the control algorithm itself, and (ii) investigate the shake table-specimen-control interaction by coupling the LHPOST6 model in Matlab/Simulink with the MTS 469D controller and a specimen model developed in a structural analysis software, such as OpenSees. •A comprehensive methodology for calibrating a multi-physics model (rigid body, dissipation, pneumatics, hydraulics, control) of a 6-DOF large-scale shake table.•Decomposing friction and nonlinear viscous damping forces from Cartesian space to the component level using the shake table system’s geometric assembly.•Strategy to calibrate nonlinear hydraulic flow–spool curves of each actuator using tri-directional triangular wave test data.•Three-phase strategy to validate a nonlinear shake table model at subsystem, open-loop, and closed-loop levels.•The calibrated LHPOST6 model enables off-line controller tuning and analysis of table–specimen dynamic interaction.